2020
DOI: 10.1016/j.hpb.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of and risk prediction model for lymph node metastasis in resectable intrahepatic cholangiocarcinoma: do all require lymph node dissection?

Abstract: Background: Lymph node (LN) metastasis portends a worse prognosis following resection of intrahepatic cholangiocarcinoma (ICC); however, lymphadenectomy is not routinely performed, as its role remains controversial. Herein, we developed a risk model for LN metastasis by identifying its predictive factors and assessed a subset of patients who might not benefit from LN dissection (LND).Methods: 210 patients who underwent curative-intent surgery for ICC were retrospectively reviewed. A preoperative risk model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 39 publications
0
16
1
1
Order By: Relevance
“…It is reported that the morbidity of ICC in male is 40-63.5% [14,[16][17][18], and the age at diagnosis is mainly in the 6th decade of life, but ranges from 21 to 86years [17][18][19][20]. Among the 68 cases in the current study, 50 were males accounting for 73.5% of the patients, which was higher than that reported in the literature.…”
Section: Discussioncontrasting
confidence: 58%
“…It is reported that the morbidity of ICC in male is 40-63.5% [14,[16][17][18], and the age at diagnosis is mainly in the 6th decade of life, but ranges from 21 to 86years [17][18][19][20]. Among the 68 cases in the current study, 50 were males accounting for 73.5% of the patients, which was higher than that reported in the literature.…”
Section: Discussioncontrasting
confidence: 58%
“…A cutoff of 1 (i.e. LNM-positive and negative) has been shown to effectively differentiate the patients’ prognoses [ 10 , 12 , 20 , 30 33 ]. This conclusion was verified in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…LNM positivity and negativity, which are defined as N0 and N1, have been proven to effectively differentiate the prognosis of ICC. 17,[24][25][26][27] The N stages for other bile duct cancers, namely extrahepatic cholangiocarcinoma, perihilar cholangiocarcinoma, and gallbladder carcinoma, are all graded with LNM numbers. 21 Nakagawa et al proposed a new N stage system: N0 (LNM 0), N1 (LNM 1-2), and N2 (LNM > 2), in 2005, in which survival of patients with N2 status was worse than that of patients with N1 status.…”
Section: Discussionmentioning
confidence: 99%
“…LNM positivity and negativity, which are defined as N0 and N1, have been proven to effectively differentiate the prognosis of ICC. 17,2427 The N stages for other bile duct cancers, namely extrahepatic cholangiocarcinoma, perihilar cholangiocarcinoma, and gallbladder carcinoma, are all graded with LNM numbers. 21 Nakagawa et al.…”
Section: Discussionmentioning
confidence: 99%